Business Process Reengineering for Inventory Module Manufacturing Company using Odoo V12.0 Application - Kadek Alit Sudiyana; I Made Sukarsa; I Made Sunia Raharja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2021)
The use of Enterprise Resource Planning system in manufacturing companies aims to increase the companies’ productivity. In this case, an integrated ERP system could maximize the companies’ production. Thus, the researcher conducted a study that discussed the application of ERP Odoo V12.0 system in a chicken company. This research focused on inventory sectors. There is no special system to manage the inventory section. The business process reengineering that has been done were the automatic purchase process, a special system or module to manage the inventory, the transfer of blast freezing process to manufacturing module, and the inventory reports. Based on the system testing by using User Acceptance Test that has been done, the researcher received quite good responses. In this case, the scores obtained for the Inventory 1215 from 1760 (positive result). Keywords : Business Process Reengineering, Enterprise Resource Planning, Odoo V12.0, Inventory, User Acceptance Test